Juvenile Myelomonocytic Leukemia - Imtiaz, Amna; Naseem, Lubna; Ali, Sundas (International Journal of Pathology, 2018)
Juvenile Myelomonocytic Leukemia (JMML), which comes under the WHO category of Myelodysplastic/Myeloproliferative Neoplasms, is a rare aggressive hematological malignancy of early childhood caused byexcessive proliferation of cells of monocytic and granulocytic lineages. The peripheral blood shows leukocytosis,thrombocytopenia and anemia. The majority of patients present with infection. Hematopoietic Stem CellTransplantation (HSCT) is the best treatment option available. Here we present a case of a one year old femalechild who presented with complaints of fever, cough and progressive pallor for the last six months andabdominal distention associated with vomiting, diarrhea and sub-conjunctival hemorrhages for past 2 months.The fever did not respond to medication. She developed sepsis and intracranial bleed and expired on the 10th dayof hospitalization